Availability of Waqf System in Support of Development of Three Dayah Education in Aceh - Ruslan Razali; Amiruddin Amiruddin (STAI Hubbulwathan Duri, 2022)
This research examines the role of the availability of waqf systems in supporting the development of three-dayah education in Aceh. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Islam as a religion of rahmatan lil alamin and bring peace governs all patterns of human life, starting its relationship with Allah (habluminallah) and its relationship with humans (habluminannas). Learning the teachings of Islam means requiring teaching, teaching is obtained in the institute of education. Traditional educational institusions commonly dayah still show their exclusitivity until now because it is supported by the availability of waqf. The results showed that in three Dayah Aceh, namely Dayah MUDI and Dayah Daarul Huda utilizing waqf property for the availability of learning rooms and teacher dormitories to support education development. Dayah Ashasul Islamiyah develops waqf property to increase economic value and social welfare through the utilization of shrimp ponds. The positive impact of the availability of waqf in three dayah in Aceh is the increase in student achievement and welfare for teachers.